Analysis Of Handover Planning In Wideband Code Division Multiple Access (W–CDMA) - Indra, Win Adiyansyah; Sukumaran, Saravanan; Mohd Annuar, Khalil Azha; -, Irianto (Medwell Journals, 2019)
This study analysed the most suitable handover type for Wideband Code Division Multiple Access (W-CDMA) system by using simulation software. Forsk Atoll, Earth Explorer and Global Mapper 15 were used to do the simulations, local area (Bukit Beruang, 2.240°N102.279°E to Bukit Baru, 2.222°N102.275°E) was selected based on the its varies altitudes, high density, high traffic, etc. The simulation result showed that by implementing soft handover in W-CDMA system, the users will experience no drop call during handover from one cell to another cell. The Received Signal Strength Indicator (RSSI) range value between -80 to -100 dBm in all selected area which considered as good signal strength range. There’s no blank spot. Physical measurement in the field (selected area), like drive test, particularly in the handover areas, borders of every cells is required to verify the simulation results, the data from physical measurement in the field must be considered and key in inside the simulation software, so that, the revised or new results will have a high validity.